Pay-What-You-Want in Competition - Margaret Samahita (Lund University, School of Economics and Management, Department of Economics, 2015)
Pay-What-You-Want (PWYW) pricing schemes are popular in certain industries and not others. We model the seller's choice of pricing scheme under various market structures assuming consumers share their surplus. We show that the profitability and popularity of PWYW depend not only on consumers' preferences, but also on market structure, product characteristics and sellers' strategies. While there is no equilibrium where PWYW dominates the market, given a sufficiently high level of surplus-sharing and product differentiation, it is chosen by the second mover to avoid Bertrand competition. The equilibrium results and their associated market characteristics are consistent with empirical examples of PWYW.
Keywords: D11; D42; D43; L11; L12; L13; 330; Pay-what-you-want; competition; product differentiation; market behavior; market structure